Phage-Microbiota Interactions in the Gut: Implications for Health and Therapeutic Strategies - Naderian, Ramtin; Alibabaei, Farnaz; Paraandavaji, Elham; Dehghan, Parmida; Eslami, Majid (Probiotics and antimicrobial proteins, 2025)
The diversified ecology of microorganisms, including bacteria, archaea, fungi, protozoa, and viruses known collectively as the gut microbiota, which includes bacteriophages, is crucial to human health because it affects functions like immune system regulation, vitamin production, and pathogen protection. Bacteriophages are viruses that infect bacteria and are increasingly recognized as a viable treatment option for antibiotic-resistant strains, owing to their high host specificity, which enables precise targeting of drug-resistant bacteria while sparing commensal microbiota. The complex relationships between bacteriophages and gut microbiota are examined, with emphasis on their roles in maintaining health and contributing to disease. Gut microbiota homeostasis is influenced by a number of factors, including age, nutrition, and drugs. Bacteriophages, via lytic cycles and lysogenic conversion, influence the gut microbiota composition and microbial community structure. Gaining an understanding of these processes is crucial to appreciating their contribution to the stability and variety of microbes. Recent research highlights the gut phageome's potential for therapeutic interventions by demonstrating its substantial influence on immunological responses and metabolic problems. The study of phage-microbiota interactions has been transformed by cutting-edge technologies, including high-throughput sequencing, CRISPR-Cas systems, and viral metagenomics, which allow for thorough research and the creation of new therapeutics. Even though tailored medicine and pathogen management hold great potential, obstacles such as regulatory difficulties and bacterial resistance call for additional investigation. Phage-based therapeutic strategies are rapidly advancing, ranging from genetically engineered phages and phages with modified capsid proteins designed to enhance efficacy to phage cocktails that target multiple bacterial strains.